Parâmetros nutricionais pré-operatórios para pacientes após cirurgia bariátrica - Jamil, Liliane Carvalho [UNIFESP] (2019)
Introduction: Surgical outcomes in post bariatric patients are strongly influenced by the patient's nutritional status. Despite the extensive literature, in practice, follow-up management and nutritional preparation for bariatric patients undergoing subsequent surgeries present great variation. There is a need to standardize and summarize post bariatric nutritional recommendations in order to optimize preparation of patients for following surgeries. Objective: To define the preoperative nutritional parameters for post bariatric patients and create an assessment tool based on the current recommendations. Method: A review of the literature was carried out in the Health Information databases of the National Library of Medicine (MEDLINE), the electronic library of the Electronic On-line Library (SciELO) in Latin American and Caribbean Literature in Health Sciences (LILACS and Embase from January 2008 to October 2018 with use of the following terms: bariatric surgery, nutritional status, trace elements, nutritional physiological phenomena, postoperative care, postoperative period. The agreement between two examiners was evaluated using the Kappa coefficient. The content of the selected articles was submitted to the thematic analysis. Recommendations found in this review were organized to create an assessment tool. Results: Recommendations regarding routine testing, prophylactic and therapeutic supplementation and multidisciplinary follow-up for post-bariatric patients were identified in the literature. Conclusion: Preoperative nutritional parameters for post bariatric patients were defined and organized in an assessment tool.